Análise do discurso institucionalizado da escola e do professor : uma dialética entre normas, saberes e atividade formadora - Passamani, Susimara Fagundes (2015)
This search, entitled Analysis of the institutionalized speech of the school and the teacher in the school environment: a dialectic among rules, knowledge and forming activities, it delimits to the language and work thematic, more specifically as regards the situation of enunciation of the educational agents inserted in school, through the limited speech in the documents denominated Curricular Organization and Methodological Procedures of Approach of the Contents and Plans of Study of the 3rd Grade of High School, observed in three state schools from Itaqui, RS. It justified the study and the thematic due to the social relevance of better understand institutionalized speeches in the school environment and the management of the use of oneself of the teacher in the activity. The objective is to describe and analyze the limited speeches in the institutional documents and in the language practices of the teacher in the activity, through interviews realized with coordinators and teachers, trying to understand the complexity of the prescribed and of the possible renormalizations in the labor activity, through the verbal, interaction that come true through scenography and the discursive ethos built in the realization of the activity in the school environment. The theoretical approach emphasizes to the ergologic studies (SCHWARTZ, 2010a, 2010b, 2011a, 2011b) through interface with the dialogism in Bakthin/Volochinov (2006) and the linguistic-speech concepts of the scenography an of the ethos (MAINGUENEAU, 2002, 2008a, 2008b). The search is an exploratory and documental type, developed through the study of multiple cases procedure, with qualitative approach in analysis. In order to account to meet the goals of this search, stand out scenography in the speech of the school and the teacher that emphasize prescription to the teaching practice of the teacher from where emanate built images that originate a discursive ethos of the assertion in documental case, and of an "obedient/disciplined" teacher, with regard to teaching subject